Function space analysis for the prison and penal farm in the Philippines - Kangkhao, Surasak 1961- (1989)
This study assesses and evaluates the Bureau of Prison's aims and objectives. It tackles reforms of the physical aspects of the prison buildings which are based on the principles of Human Rights and situations and civic organizations in the local site. With the assessment, the architects may come up with a design that could maximize movement among the users in terms of spaces requirements and space matrix. A design also to serve as a tool for self-improvement.
Vita.
Thesis (Master of Architecture : Architectural Design)--University of the Philippines, Diliman
Keywords: Correctional institutions -- Philippines; Prisons -- Construction -- Philippines